Antidiabetic in vitro and in vivo evaluation of cyclodipeptides isolated from Pseudomonas fluorescens IB-MR-66e. (8th May 2019) - Lozano-González, M.; Ovalle-Magallanes, B.; Rangel-Grimaldo, M.; De la Torre-Zavala, S.; Noriega, L. G.; Tovar-Palacio, C.; Tovar, A. R.; Mata, R.
Abstract : Cyclodipeptides cyclo(l -Pro-l -Leu), 1 ; cyclo(l -Pro-l -Val), 2 ; and cyclo (l -Pro-l -Phe), 3 from Pseudomonas fluorescens IB-MR-66e showed α-glucosidase inhibitory activity. Abstract : Three cyclodipeptides [cyclo(l -Pro-l -Leu), 1 ; cyclo(l -Pro-l -Val), 2 ; and cyclo(l -Pro-l -Phe), 3 ] were isolated from Pseudomonas fluorescens IB-MR-66e. The structures were established by spectral means and corroborated by synthesis. The antidiabetic potential of compounds1–3 was explored in vivo, in vitro and in silico . The three peptides showed important inhibitory activity against the α-glucosidase enzyme. Further analysis in vivo using a sucrose tolerance test corroborated that compounds1 and3 (1–30 mg kg −1 ) significantly reduced the postprandial state. Peptide1 (1–30 mg kg −1 ) also reduced the postprandial peak after a glucose challenge and exhibited significant hypoglycemia during an insulin tolerance test; thus, its antidiabetic action involved also an improvement of insulin utilization not related to Akt phosphorylation nor to an increment in mitochondrial bioenergetics nor insulin secretion.